2011
DOI: 10.1111/j.1365-2419.2011.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of larval fish assemblages from the inner shelf into the East Australian Current and into the western Tasman Front

Abstract: Entrainment and transport of larval fish assemblages by the East Australian Current (EAC) were examined from the coastal waters of northern New South Wales (NSW) to the western Tasman Front, via the separation of the EAC from the coast, during the austral spring of 2004. Shore-normal transects from the coast to the EAC off northern NSW revealed an inner shelf assemblage of near-shore families (Clupeidae, Engraulidae, Platycephalidae and Triglidae), an EAC assemblage dominated by Myctophidae and Gonostomatidae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…The inner-shelf water in this region has previously been shown to be distinctively enriched in nitrate (Suthers et al 2011), phytoplankton (Condie et al 2011), zooplankton , and larval fish (Mullaney et al 2011;Syahailatua et al 2011a). In this study, satellite imagery showed the inner-shelf water to have enhanced levels of Chl a (.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…The inner-shelf water in this region has previously been shown to be distinctively enriched in nitrate (Suthers et al 2011), phytoplankton (Condie et al 2011), zooplankton , and larval fish (Mullaney et al 2011;Syahailatua et al 2011a). In this study, satellite imagery showed the inner-shelf water to have enhanced levels of Chl a (.…”
Section: Discussionsupporting
confidence: 54%
“…A region of mixed EAC, Tasman Sea, and coastal water exists off the coast of Sydney and over 100 km offshore , known as the western Tasman Front (wTF; Mullaney et al 2011). The cyclonic eddy observed here is part of the same process forming the wTF and its mixture of water types.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations